Warring tautologies: moral dissent from a cognitivist perspective - Matthias Kiesselbach (Ethic@: an International Journal for Moral Philosophy, 2009)
It is commonly thought that the prevalence of moral dissent poses a problem for the moral cognitivist, forcing her to diagnose either a lot of misunderstanding, or a lot of unexplained observational error. Since mere misunderstanding can be ruled out in most cases of moral dissent, and since the diagnosis of widespread unexplained error is interpretively unstable, prevalent dissent has pushed many philosophers towards non-cognitivism. In this essay, I argue that once a diachronic, pragmatist theory of language along the lines of the latest Wittgenstein is employed, a third interpretive option becomes available to the cognitivist. Besides the diagnostic options of misunderstanding and factual disagreement, she can argue that a given case of moral dissent is an instance of grammatical tension. This interpretation not only saves moral cognitivism, it also has some attractive theoretical implications. Among other things, it yields an elegant way of solving the current debate around moral particularism.